MENGIDENTIFIKASI CARA BERPIKIR DEDUKTIF DAN INDUKTIF DALAM TEKS BACAAN MELALUI PENGETAHUAN KOTEKS DAN REFERENSI PRAGMATIK - ., Izhar (JURNAL PESONA, 2016)
Identifying deductive and inductive thinking in reading has been popular because human thinking is based on both of them. The problem is students from primary and secondary shool up to higher level often get difficulty to identify deductive and inductive thinking. A text is not released from reference and contex which can explain that thinkings. This study aims to explain and find the concrete knowledge that determine whether a text is written using deductive or inductive thinking. The result shows that reference and context deliver deductive and inductive thinking in reading.Keywords: deductive, inductive, reading text, contex, pragmatic reference.